Community efficacy for non-communicable disease management (COEN): Conceptualization and measurement. - Shangzhi Xiong; Gangjiao Zhu; Rahul Malhotra; Xinyue Chen; Enying Gong; Zhan Wang; Jian'An Zhang; Weixia Peng; Shiwei Wang; Xurui Jin; Nicholas Peoples; Truls Østbye; et al. (Public Library of Science (PLoS), 2024)
The importance of community-based non-communicable disease (NCD) management has been internationally recognized. However, currently, no instrument is available to evaluate a community's ability to provide NCD management for its residents. This study defined such an ability as "Community Efficacy for NCD Management" (COEN), and aimed to conceptualize, develop and validate a scale to measure COEN. We first conducted literature review, expert interviews, and Delphi panels to conceptualize COEN and select scale items. Then, we conducted two rounds of community surveys and interviews to validate the COEN scale among local residents in three cities in China. We used Cronbach's alpha to test the scale's internal consistency, Kappa test for test-retest reliability, and exploratory factor analysis for structural validity. COEN was conceptualized as "the ability of a community to provide NCD management for its residents, reflected by its natural environment, social relationships, community resources, health services, and resident-engaging activities." The first community research among 345 residents yielded a 38-item COEN scale with high internal consistency (Cronbach's alpha = 0.86) and acceptable test-retest reliability (Kappa value >0.2). The second community research tested a shortened COEN scale among 657 residents, yielding a final COEN scale with 14 items from five factors: community management (n = 3), social relationships (n = 4), resource accessibility (n = 3), community health services (n = 2), and resident engagement (n = 2), with an overall Cronbach's alpha of 0.79. COEN is a meaningful concept in contextualizing and evaluating NCD management anchored in the community, and the COEN scale is a multi-domain reliable tool to quantify COEN, which can be used to guide future related research and practice in public health.